1990
DOI: 10.1002/path.1711600113
|View full text |Cite
|
Sign up to set email alerts
|

Impaired chemotactic responses of bronchoalveolar leukocytes in experimental pneumocniosis

Abstract: Rats were exposed to clouds of the following pneumoconiotic dusts: quartz, coal-mine dust, and chrysotile asbestos at 10 or 50 mg/m3 for 8, 32, and 75 days; for comparison, rats were also exposed to the non-pathogenic dust titanium dioxide (TiO2). The bronchoalveolar leukocytes (macrophages and neutrophils) from dust-exposed and control rats were obtained by lavage and tested for their ability to migrate toward zymosan-activated serum. Varying amounts of neutrophils were present depending on the ability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…TiQ dust is commonly used as a negative control dust in studies of pulmonary fibrosis [9,10,23]. Consistent with the hypothesis that NAGase concentration in lavage fluid reflects the fibrogenic potential of instilled dusts, generic anthracite and bituminous dust exposures produced NAGase responses that were more similar to the TiO 2 than to the quartz dust response.…”
Section: Discussionsupporting
confidence: 50%
“…TiQ dust is commonly used as a negative control dust in studies of pulmonary fibrosis [9,10,23]. Consistent with the hypothesis that NAGase concentration in lavage fluid reflects the fibrogenic potential of instilled dusts, generic anthracite and bituminous dust exposures produced NAGase responses that were more similar to the TiO 2 than to the quartz dust response.…”
Section: Discussionsupporting
confidence: 50%
“…However, it may be due to the toxicity of the PM 10 particles and/or overload which would both restrict macrophage movement via the cytoskeleton (Möller et al 2002). Other pathogenic particles have been found to inhibit macrophage chemotactic activity following in vivo exposure (Donaldson et al 1990). Neutrophils closely situated to macrophages in the bronchoalveolar space during inflammation may release factor(s) that inhibit macrophage membrane-related functions such as phagocytosis, chemotaxis and spreading, and this may also provide an explanation (Donaldson et al 1988(Donaldson et al , 1989).…”
Section: Discussionmentioning
confidence: 98%
“…The results of the present study revealed that exposure to cement dust, decreased the physiological activity of PMNs as measured by decreased CL response in cement mill workers. The previous studies by Scheuchenzuber et al [20], Hermanowicz et al [21], Donaldson et al [22] and Sliwinski et al [23] focused directly or indirectly on the phagocytic function and dust but none of them concerned the cement mill workers. In the present study, the phagocytic function of PMNs stimulated with OPZ was signifi cantly decreased in cement mill workers, compared to controls (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…They found a marked impairment of the chemotactic function of neutrophils stimulated with zymosan-activated serum in all the groups of workers exposed to organophosphate pesticides. Similarly, Donaldson et al [22] conducted a study on rats exposed to clouds of the pneumoconiotic dusts including quartz, coal-mine dust, and chrysotile asbestos for 8, 32, and 75 days. For comparison, the rats were also exposed to the non-pathogenic dust of titanium dioxide (TiO2).…”
Section: Cement Dust Exposure and Chemiluminescence Response O R I G mentioning
confidence: 99%